2019
DOI: 10.1038/s41598-019-56005-w
|View full text |Cite
|
Sign up to set email alerts
|

Pectic Oligosaccharides from Cranberry Prevent Quiescence and Persistence in the Uropathogenic Escherichia coli CFT073

Abstract: Urinary tract infections (UTIs) caused by Escherichia coli create a large burden on healthcare and frequently lead to recurrent infections. Part of the success of E. coli as an uropathogenic bacterium can be attributed to its ability to form quiescent intracellular reservoirs in bladder cells and its persistence after antibiotic treatment. Cranberry juice and related products have been used for the prevention of UTIs with varying degrees of success. In this study, a group of cranberry pectic oligosaccharides (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Comparisons of 2D NMR spectra indicated that the structural features of uG4 m3 were representative for the Cranf1b-cPOS unsaturated methyl poly-galacturonoate series. The authors [133] observed that the formation of the 4,5-unsaturated bond in the Cranf1b-cPOS oligomers may have been due to eliminative cleavage resulting from the specific types of enzymes used to commercially process cranberry materials, further supporting the need for additional research into cranberry pectin structures and the effects of processing (see Section 1.2). by HPLC to obtain two compounds and the fraction HDP-cPOS, composed of a series of unsaturated methyl polygalacturonoates with DP 3-8 and one or two free carboxylic acid groups.…”
Section: Cranberry Pectins: Occurrence and Structuresmentioning
confidence: 96%
See 4 more Smart Citations
“…Comparisons of 2D NMR spectra indicated that the structural features of uG4 m3 were representative for the Cranf1b-cPOS unsaturated methyl poly-galacturonoate series. The authors [133] observed that the formation of the 4,5-unsaturated bond in the Cranf1b-cPOS oligomers may have been due to eliminative cleavage resulting from the specific types of enzymes used to commercially process cranberry materials, further supporting the need for additional research into cranberry pectin structures and the effects of processing (see Section 1.2). by HPLC to obtain two compounds and the fraction HDP-cPOS, composed of a series of unsaturated methyl polygalacturonoates with DP 3-8 and one or two free carboxylic acid groups.…”
Section: Cranberry Pectins: Occurrence and Structuresmentioning
confidence: 96%
“…The use of multiple fraction names to describe essentially the same material has already led to some confusion regarding which cranberry materials and subfractions can be appropriately compared for even the relatively few studies investigating cranberry oligosaccharides to date [25][26][27][28][29]72,[112][113][114][115][131][132][133]. Insufficient material descriptions are also a problem as a minimal standardized method for characterizing and describing oligosaccharide fractions has yet to be established (see Table. Original, author-assigned fraction names have been used when possible but some (italics) have been elaborated upon or added to by the current authors to facilitate discussion.…”
Section: Characteristics Of Xyloglucan Fractions Used By Various Studiesmentioning
confidence: 99%
See 3 more Smart Citations